El trabajo autónomo y su incumplimiento de la norma constitucional que prohíbe toda forma de confiscación de sus productos, materiales o herramientas de trabajo - Torres Carrión, Stalin Santiago (2022)
The present thesis of degree is entitled "Autonomous work and its failure to comply with the constitutional norm that prohibits any form of confiscation of its products, materials or tools of work, infringed by municipal ordinances", the interest in the development of this thesis topic is to carry out a study on the subject in question because it is a latent reality manifested day by day in the squares, markets and streets of the cities of all the municipalities of Ecuador generating serious affectations to the economy of the self- employed. The study shows that the violations of the rights of self-employed workers are one of several forms of violence towards workers that allow to generate an altered state of consciousness by psychological violence and physical violence making sellers not abandon their profession and informality and on the contrary their situation worsens as they only borrow more to be able to continue working and buy more merchandise than was confiscated by the members of the municipal police, The present investigation therefore seeks to recover the scope of this constitutional right that has been desecrated by the municipal authorities. In this thesis materials or methods that allowed the development of this research were applied, as well as surveys and interviews with legal professionals and municipal authorities, these results served to raise the project of legal reform to the Organic Code of Territorial Organization, Administration and Decentralization in order to avoid any form of confiscation of goods or work tools of the self-employed that violates their constitutional